Reconstruction of the Integrated Online Investigation Legal Policy for Online Fraud with Victims Located Outside the Police Jurisdiction Area - Arham Gusdiar; Ekawati Ekawati; Kif Aminanto (Indonesian Journal Publisher, 2026)
The development of digital technology has led to an increase in cross-border, anonymous, and electronically based online fraud crimes, giving rise to various legal issues in the investigation process, particularly when the victim is located outside the jurisdiction of the police authority where the perpetrator committed the crime. This study aims to analyze the legal provisions governing the investigation of cross-provincial online fraud crimes within the Indonesian legal system, examine the empirical and juridical problems encountered in investigative practices, and formulate a reconstruction of an integrated online investigation legal policy based on legal certainty and digital technology. This study employs a normative legal method with a statutory and conceptual approach through an analysis of the Criminal Code (KUHP), the Criminal Procedure Code (KUHAP), the Electronic Information and Transactions Law (UU Informasi dan Transaksi Elektronik), the Law on the Indonesian National Police (Polri), and various regulations related to handling cybercrime. The results show that the applicable investigative system is still oriented towards the conventional crime paradigm and is therefore unable to accommodate the rapid, cross-border, and digital technology-based character of cybercrime. The key problems include difficulties in determining the locus delicti and tempus delicti, overlapping authority between police regions, weak investigative coordination, limited digital forensics, slow account blocking, and poor integration of the national cyber case database. Therefore, legal policy reconstruction is needed through the establishment of an integrated cyber investigation system based on real-time investigations, strengthening cyber jurisdiction, integrating the national cyber case database, strengthening inter-agency interoperability, and legitimizing the use of artificial intelligence, cyber patrols, and digital tracking in the investigation process to create a modern, effective, and adaptive law enforcement system capable of providing legal certainty and optimal protection for victims of online fraud across provinces in Indonesia.